2004
DOI: 10.1088/0954-3899/30/2/003
|View full text |Cite
|
Sign up to set email alerts
|

On the density-dependent hadron field theory at finite temperature and its thermodynamical consistency

Abstract: In this work we study in a formal way the density dependent hadron field theory at finite temperature for nuclear matter. The thermodynamical potential and related quantities, as energy density and pressure are derived in two different ways.We first obtain the thermodynamical potential from the grand partition function, where the Hamiltonian depends on the density operator and is truncated at first order. We then reobtain the thermodynamical potential by calculating explicitly the energy density in a Thomas-Fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The prototype of such theory is Quantum Hadrodynamics (QHD) [20,21], which has been shown to describe well many properties of nuclear matter, finite nuclei and neutron stars [20,21,23,24,25,26,27]. This theory can be extended to include many-body correlations as density-dependent meson couplings [28,29]. The successful description of nuclear properties indicates that the essential aspects of low energy strong interactions are well described by QHD.…”
Section: Introductionmentioning
confidence: 99%
“…The prototype of such theory is Quantum Hadrodynamics (QHD) [20,21], which has been shown to describe well many properties of nuclear matter, finite nuclei and neutron stars [20,21,23,24,25,26,27]. This theory can be extended to include many-body correlations as density-dependent meson couplings [28,29]. The successful description of nuclear properties indicates that the essential aspects of low energy strong interactions are well described by QHD.…”
Section: Introductionmentioning
confidence: 99%
“…The important range of temperature which is discussed lies between 10 and 150 MeV since the liquid-gas phase transition takes place around 10 MeV, the phase transition from hadronic to quarkionic matter around 150 MeV and the relevant temperatures in the cooling of a protoneutron star after a supernova explosion takes place go up to approximately 40 MeV [16]. In this work we discuss another possible application of the formalism we have derived in [14,15] in order to incorporate temperature effects in the study of lagrangians with BR scaling.…”
Section: Introductionmentioning
confidence: 99%
“…We have already shown that one of these density dependent models, to which we refer as TW model [12,13], originally derived at T = 0 can be extrapolated to finite temperatures once the thermodynamical consistency remains unaltered [14,15]. The important range of temperature which is discussed lies between 10 and 150 MeV since the liquid-gas phase transition takes place around 10 MeV, the phase transition from hadronic to quarkionic matter around 150 MeV and the relevant temperatures in the cooling of a protoneutron star after a supernova explosion takes place go up to approximately 40 MeV [16].…”
Section: Introductionmentioning
confidence: 99%
“…This term guarantees the thermodynamical consistency and the energy-momentum conservation. For more detailed calculations, at zero and finite temperatures, please refer to [41].…”
Section: The Tw Density Dependent Hadronic Modelmentioning
confidence: 99%